1996
DOI: 10.1002/(sici)1096-9861(19961104)375:1<89::aid-cne6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Distributed representation of vibrissa movement in the upper layers of somatosensory cortex revealed with voltage-sensitive dyes

Abstract: We have identified large-scale patterns of electrical activity in circuits that occur in response to stimulation of peripheral receptors. Our focus was on primary (S1) vibrissal cortex of anesthetized rat, and we used optical techniques in conjunction with voltage-sensitive dyes to measure depolarization of the upper layers of cortex. Displacement of one vibrissa produced a field of activity that extends over very many cortical columns in S1. There are multiple, focal maxima within this field. A global maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
123
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(143 citation statements)
references
References 61 publications
20
123
0
Order By: Relevance
“…This finding, using a variety of stimulus types, is in congruence with the findings of Petersen et al (2003), in which it is also shown by histology that the VSD activity originates at the center of the corresponding barrel (Kleinfeld and Delaney, 1996).…”
Section: The Early Depolarizationsupporting
confidence: 88%
See 3 more Smart Citations
“…This finding, using a variety of stimulus types, is in congruence with the findings of Petersen et al (2003), in which it is also shown by histology that the VSD activity originates at the center of the corresponding barrel (Kleinfeld and Delaney, 1996).…”
Section: The Early Depolarizationsupporting
confidence: 88%
“…2, 4) and by Takashima et al (2001). In contrast, Kleinfeld and Delaney (1996) detected a triphasic response, but without the net hyperpolarization.…”
Section: The Surround Hyperpolarizationmentioning
confidence: 88%
See 2 more Smart Citations
“…This may represent the initial step in the cortical integration of afferent sensory signals from several whiskers. This proposal is supported by in vivo 2-deoxyglucose mapping and imaging studies showing that the tangential spread of excitation occurs indeed at the level of layer 2/3 (McCasland and Woolsey, 1988;Kleinfeld and Delaney, 1996;Woolsey et al, 1996). Finally, layer 2/3 pyramidal cells can excite layer 5 pyramidal cells, the principal output neurons of the neocortex (Thomson and Bannister, 1998;Reyes and Sakmann, 1999).…”
Section: Supragranular Layersmentioning
confidence: 78%